Potential Use of Shorea leprosula for Rehabilitation of Degraded Tropical Production Forest Ecosystems - Attarik, Nuriskia; Pamoengkas, Prijanto; Rachmat, Henti Hendalastuti; Susilowati, Arida (Jurnal Sylva Lestari, 2024)
The diverse forests in Indonesia require proper management to preserve their delicate ecosystems. Limited production forests (HPT) are prone to damage and require careful rehabilitation to restore them to their original state. Native tree species such as Shorea leprosula are essential for the success of land and forest rehabilitation in HPT areas. This study aimed to assess the potential of S. leprosula species for HPT rehabilitation by examining its growth in the Gunung Dahu Research Forest (GDRF) by measuring the percentage of live plants, tree growth, and soil improvements under S. leprosula stand in sloping land. The results showed that S. leprosula had fast (1.25 cm/year) to very fast (1.79 cm/year) diameter growth, a dense canopy cover with a leaf area index of 2.88, and improved soil physical (soil moisture of 55.54%, topsoil thickness of 6.2 cm, and litter thickness of 16 cm) and chemical properties (pH of 5.2, soil organic carbon of 3.85, total nitrogen of 0.3, carbon-to-nitrogen ratio of 12.8, available phosphorus of 35.3, and exchangeable potassium of 0.76). Therefore, the successful rehabilitation of S. leprosula in GDRF indicates that it can potentially rehabilitate other HPT areas with similar environmental and site conditions. Keywords: Dipterocarpaceae, fast growing, Gunung Dahu Research Forest, limited production forest, land slope